Psychological Responses Among Indonesian Nurses In The Outbreak Of Covid-19 Pandemic - Mulyanti Roberto Muliantino; Emil Huriani; Boby Febri Krisdianto; Rika Sarfika; Marnila Yesni; Endang Sulistyowati; Kristanti Wahyuningtyas; Ucip Sucipto; R.Ade Sukarna; Eko Prasetyo; Khatijah Binti Abdullah (Journal of Nursing Care, 2021)
An unprecedented outbreak of the newly emerging infectious disease of Covid-19 with rapid increases globally and in Indonesia may result in psychological distress among nursing staff. The present study aimed to identify psychological responses among nurses in the Covid-19 pandemic in Indonesia. A cross-sectional data were collected from 535 nurses working in 119 hospitals from 24 provinces in Indonesia using Depression Anxiety Stress Scale (DASS-42) and sociodemographic questionnaire. Data were collected using an online survey and analyzed with descriptive and Chi-squared tests. Analysis showed among the respondents, 23.7% (n = 127) had moderate anxiety, 6.5% (n = 35) had moderate stress and 8.8% (n =47) had moderate depression. Anxiety, stress, and depression were significantly higher among nursing staff in the emergency department and Covid-19 isolation ward. Nursing staff, especially those working in the departments mentioned above, were more susceptible to psychological impairment. Effective strategies toward improving their psychological status should be provided among the nurses.Keywords: Covid-19 pandemic, psychological responses, work stress